BUSINESS SIMULATIONS AS A COMPONENT OF AN INNOVATIVE MODEL OF MODERN ECONOMIC EDUCATION - Aliyev, Oktay (Proceedings of National Aviation University (archive), 2016)
Purpose: In the article there has substantiated the author’s research viewpoint on understanding the essence of the notions of «innovation», «innovative model of development», specified the role and importance of innovation development of modern economic education in Ukraine as an important factor of economic socialization of people, as a powerful factor in improving the quality of human capital. Methods: In the article there has been used the method of terminological analysis to determine the essential content of the notions «innovation», «innovative model of development», «business simulation in higher economic education»; the observational methods (incorporated and indirect surveillance) to typify the experience of training of future specialists in Economics in higher domestic economic institutions, including the Academician Yuriy Bugay International Scientific and Technical University (MNTU). Results: The author suggested the definition of essence of the meaning of the notion «business simulation in higher economic education» being an innovative computer programs that simulate the real economic environment and enable the future professionals in the sphere of economy to acquire knowledge and skills in doing entrepreneurship and business so that they could practically apply them in both the process of virtual learning and in the real professional activity. The performed in article examination of the experience of training of future specialists majoring in Economics in the domestic tertiary economic institutions, including the Academician Yuriy Bugay International Scientific and Technical University (MNTU), enabled the author to rationalize the actuality of introducing business simulations in the educational process of higher economic establishments. According to the author’s opinion, the introduction of online programs in the educational process of higher educational institutions of Ukraine enables not only the creation of highly automated working environment of the future specialist-economist, but it is promising in terms of implementing innovative model of economic education for it provides real opportunities to students at the study stage at the higher economic educational institutions to have access to the latest innovative information in any form (text, graphics, audio, video, images, etc.). Discussion: There has been substantiated that the business simulation being an innovative method of teaching economics in higher economic education establishments creates a situation which is close to the real settings of professional activity, and, at the same time, the environment of the simulation has been modeled with consideration of real market rules (diminishing returns, supply and demand, additional cost competition, «outflow» of capital, etc.).